Anti-inflammatory Activity of Taro Stem Ethanol Extract (Colocasia esculenta (L.) Schott) In Vitro - Arinda Nur Cahyani; Adi Susanto; Eko Hidayaturrohman Khumaeni; Indira Pipit Miranti; Febia Citraeni; Ratih Widiyanti (Sean Institute, 2023)
Inflammation is a complex response of vascular tissue to hazards such as pathogens, irritants, and damaged cells/tissues. Inflammation is caused by the release of chemical mediators from damaged tissue and cell migration. The purpose of this study was to determine the efficacy of ethanol extract of taro stem (Colocasia esculenta (L.) Schott) which is used as an anti-inflammatory agent and to determine the concentration of ethanol extract of taro stem (Colocasia esculenta (L.) Schott) which can provide anti-inflammatory activity. The method used in this research is the stability of the red blood cell membrane. The concentrations used were 0 ppm, 25 ppm, 75 ppm, 150 ppm and 100 ppm. The results of the percentage inhibition of hemolysis stability of the red blood cell membrane of taro stem extract concentrations of 0 ppm (00.00%), 25 ppm (82.58%), 75 ppm (83.47%), 150 ppm (47.17%), 100 ppm (24.23%). Testing the anti-inflammatory activity of the ethanol extract of taro stem (Colocasia esculenta (L.) Schott) using the red blood cell membrane stability method has efficacy as an anti-inflammatory agent. The concentration of 25 ppm (82.58%) has the highest anti-inflammatory activity and with a small concentration of extract can produce great anti-inflammatory activity, compared to 100 ppm aspirin as a positive control of 24.23%. Testing the anti-inflammatory activity of the ethanol extract of taro stem (Colocasia esculenta (L.) Schott) using the red blood cell membrane stability method has efficacy as an anti-inflammatory agent. The concentration of 25 ppm (82.58%) has the highest anti-inflammatory activity and with a small concentration of extract can produce great anti-inflammatory activity, compared to 100 ppm aspirin as a positive control of 24.23%. Testing the anti-inflammatory activity of the ethanol extract of taro stem (Colocasia esculenta (L.) Schott) using the red blood cell membrane stability method has efficacy as an anti-inflammatory agent. The concentration of 25 ppm (82.58%) has the highest anti-inflammatory activity and with a small concentration of extract can produce great anti-inflammatory activity, compared to 100 ppm aspirin as a positive control of 24.23%.